ANALISIS SISTEM PENGENDALIAN INTERNAL PENGELOLAAN BARANG MILIK NEGARA BADAN NARKOTIKA NASIONAL KOTA PONTIANAK - B51107104, SUHENDRI (Jurnal KIAFE, 2014)
The research aims to find out how the system of internal control over State owned Property of National Narcotics Boards distric Pontianak city, and to find out any factors that caused the system of internal control State owned Property of National Narcotics Boards distric Pontianak city being not effective. The method used is descriptive cualitative by taking the object of research at National Narcotics Boards distric Pontianak city. Data used is Property User Authority report 2012-2013 and others data needed. Data collection techniques are documentary studies, interviews, observation, questionnaires, with data analysis techniques that evaluate organizational structure, flowcharts, internal control questionnaires, and compliance test. Based on the analysis, be concluded that the system of internal control over State owned Property of National Narcotics Boards distric Pontianak city is effective. Analysis was committed to organizational structure of National Narcotics Boards distric Pontianak city, flowchart of State owned property administration system, internal control questionnaire was given employees who involved to State owned property administration system, and compliance test to procurement of goods. However, there are several factors that may cause the system of internal control to being not effective is there is no regional internal control institution yet, limited employees, double job, unpermanent employees statue, no used statue of state owned property and land satue is leased, so it cannot recorded as asset of National Narcotics Boards distric Pontianak city. Keyword : Internal Control System, State Owned Property